Genetic Influence on Nociceptive Processing in the Human Brain—A Twin Study. (21st July 2021) - Kastrati, Gránit; Rosén, Jörgen; Thompson, William H; Chen, Xu; Larsson, Henrik; Nichols, Thomas E; Tracey, Irene; Fransson, Peter; Åhs, Fredrik; Jensen, Karin B
Abstract: Nociceptive processing in the human brain is complex and involves several brain structures and varies across individuals. Determining the structures that contribute to interindividual differences in nociceptive processing is likely to improve our understanding of why some individuals feel more pain than others. Here, we found specific parts of the cerebral response to nociception that are under genetic influence by employing a classic twin-design. We found genetic influences on nociceptive processing in the midcingulate cortex and bilateral posterior insula. In addition to brain activations, we found genetic contributions to large-scale functional connectivity (FC) during nociceptive processing. We conclude that additive genetics influence specific brain regions involved in nociceptive processing. The genetic influence on FC during nociceptive processing is not limited to core nociceptive brain regions, such as the dorsal posterior insula and somatosensory areas, but also involves cognitive and affective brain circuitry. These findings improve our understanding of human pain perception and increases chances to find new treatments for clinical pain.